Unusually Low Arcuate Artery in a Kenyan Cadaver - Thomas Amuti,; Kamau Njonjo,; Innocent Ouko,; Ibsen Ongidi; Julius Ogeng’o (The Annals of African Surgery, 2020)
The arcuate artery is one of the two major branches of the dorsalis pedis artery that supply the dorsum of the foot including interdigital spaces. The artery’s origin varies but in almost all cases it branches in the proximal third of the dorsum of the foot. During routine dissection of the right foot in a black Kenyan, we encountered a case where the artery was located and branched in the distal third of the dorsum of the foot, at the level of the metatarsophalangeal joint. This is much more distal than previously reported in prevailing literature. This artery did not give off any dorsal metatarsal arteries but gave the digital arteries directly. The dorsalis pedis artery, lateral and medial tarsal arteries had normal course in this foot.